Miss julia stirs up trouble eaudiobook Miss julia series, book 14. - Ross, Ann B. (Miss Julia, 2013)
Bestselling author Ann B. Ross cooks up a batch of fun in this latest novel in her popular series With a crisp bite in the air, Miss Julia is enjoying a well-earned respite by her new fireplace. But autumn leaves aren't the only things falling: James, Hazel Marie's housekeeper, has had a nasty tumble down some stairs. How can Hazel Marie feed and take care of him-not to mention a husband and two babies-when she barely knows how to boil water? Miss Julia jumps in to help by convincing the ladies of Abbotsville to put on their aprons and give cooking lessons. With success so close she can taste it, Miss Julia isn't thrilled when an unexpected visitor shows up. Brother Vern Puckett, Hazel Marie's no-good uncle, started life on the wrong foot and stayed there. What could he possibly want from his frazzled niece this time? With a delightful helping of madcap antics, Miss Julia Stirs Up Trouble is a perfect next course in this charming series.